Conservative management of giant omphaloceles with hydrocolloid dressings - Estefania Roldan-Vasquez, MD; Andrea Canelos, MD; Andres Caicedo, PhD; Edwin Ocaña, MD (Elsevier, 2021)
Omphalocele is a life-threatening abdominal wall defect without a treatment consensus due to its increased risk of complications. Discrepancies exist between a prompt or a delayed closure. In these cases, we present for the first time a conservative approach to close giant omphalocele lesions using hydrocolloid dressing.